Desain Mesin Pengurai Sabut Kelapa Dengan Metode Quality Function Deployment - Zulfikram Zulfikram; Hasrul Saleh; Binsar Maruli Tua Pakpahan; Rinasa Agistya Anugrah; Bambang Tjiroso (Department of Electrical Engineering, University of Patria Artha, 2023)
The aim of this research is to design a coco coir decomposition machine using the Quality Function Deployment (QFD) approach. The initial step of this research is to identify consumer needs which aims to know and answer consumer needs. The results of identifying consumer needs are used to build a House of Quality (HOQ). Based on the House of Quality (HOQ), the highest weight presentation is on the ergonomics aspect with a value of 94.5%, the size dimensions are in accordance with the average Indonesian body posture, as well as shape designs that are as needed such as non-stretching fibers. The design of the tool is designed in the form of a horizontal tube equipped with a covervalve knives, according to consumer needs, namely saving energy, tools that are easy to operate, safe, comfortable to use. This researchproduce The plan of the device measures with a device height of 130 cm, length of 195 cm and width of 70 cm